Go crazy a fun projects-based approach to Golang programming - Modrzyk, Nicolas (Apress, 2023)
Go beyond the basics of Go and build complete applications using open-source libraries or the Go programming language by Google. This book will take you deep into the memory lane of the Go language with crunchy details straight from outer space. The applications in this book include the framework for a 2D Go-based game, an image random generator Rest API, financial time series handling for trading, a Kubernetes operator, a Blockchain coding and more. You'll also get refreshers on Go constructs and useful code tricks to build performant projects, and develop an HTTP based cloud ready image generator. Each chapter will be organized in the following format: what the particular application looks like; requirements and user stories of our example program; an introduction to the Go libraries or frameworks used; and the actual implementation of the example program, including common pitfalls and their solutions.--